On a Diophantine Equation That Generates All Integral Apollonian Gaskets. (5th April 2012) - Kocik, Jerzy
Abstract : A remarkably simple Diophantine quadratic equation is known to generate all, Apollonian integral gaskets (disk packings). A new derivation of this formula is presented here based on inversive geometry. Also, occurrence of Pythagorean triples in such gaskets is discussed.